Towards being genuinely smart: 'isothermally-responsive' polymers as versatile, programmable scaffolds for biologically-adaptable materials. Issue 7 (12th December 2014) - Phillips, Daniel J.; Gibson, Matthew I.
Abstract : Thermo-responsive polymers are of broad interest in a range of biomedical and biotechnological fields. This review summaries the use of 'isothermal' transitions where thermo-responsive polymers are re-programmed to respond to other stimuli, but with the same outputs, with the aim of making them 'smarter'. Abstract : Responsive polymers have found diverse application across polymer, biomaterials, medical, sensing and engineering fields. Despite many years of study, this has focussed mainly on those polymers which undergo thermally-induced changes – either a lower or upper critical solution temperature. To rival the adaptability of Nature's macromolecules, polymers must respond in a 'smarter' way to other triggers such as enzymes, biochemical gradients, ion concentration or metabolites, to name a few. Here we review the concept of 'isothermal' responses where core thermoresponsive polymers are chemically engineered such that they undergo their useful response (such as coil-globule transition, cell uptake or cargo release) but at constant temperature. This is achieved by consideration of their phase diagram where solubility can be changed by small structural changes to the end-group, side-chain/substituents or through main chain modification/binding. The current state-of-the-art is summarised here.